First records of two Triplax species (Coleoptera, Erotylidae) from Kazakhstan. Report 2 - Temreshev, Izbasar I. (Acta Biologica Sibirica, 2025)
Pleasing fungus beetles (Erotylidae) Triplax rufipes (Fabricius, 1787) and Triplax scutellaris Charpentier, 1825 is firstly recorded from Kazakhstan. A new key to known species of the genus Triplax from Kazakhstan is given. The finds of T. rufipes from North Kazakhstan are currently new record for this species for Kazakhstan and Central Asia. Mealy oyster Ossicaulis lignatilis (Pers.) Redhead & Ginns mushroom were first recorded from Kazakhstan for T. rufipes and T. scutellaris.